2009
DOI: 10.1016/j.ejvs.2009.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Conversion to Open Repair after Endovascular Aneurysm Repair: Causes and Results. A French Multicentric Study

Abstract: Open conversion, and, in particular, PC and urgent SC, was associated with a poor outcome. According to the literature, mortality after elective SC is low but remains high in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…11 Although most reinterventions were endovascular, 4% underwent OC with a 20% mortality rate, which is consistent with the results of the current study as well as those of other contemporary series with mortality rates of 17% to 25%. 5,12 The outcomes are worse when OC is required for an emergency situation, such as rupture. In the present study, 12 patients presented with rupture and underwent OC, with a 33% mortality.…”
Section: Discussionmentioning
confidence: 98%
“…11 Although most reinterventions were endovascular, 4% underwent OC with a 20% mortality rate, which is consistent with the results of the current study as well as those of other contemporary series with mortality rates of 17% to 25%. 5,12 The outcomes are worse when OC is required for an emergency situation, such as rupture. In the present study, 12 patients presented with rupture and underwent OC, with a 33% mortality.…”
Section: Discussionmentioning
confidence: 98%
“…[7] Experience and new stent graft systems reduce this requirement to below 1%. [8][9][10] Yavuz et al [11] also reported this problem in their study.…”
mentioning
confidence: 60%
“…8 Graft migration and type I endoleak are the most frequent causes of incomplete aneurysm sac exclusion and inappropriate stentgraft positioning. 7 Severe angulations and aortic tortuosity can often lead to graft migration, while the poor quality of the proximal aortic neck (i.e., short length, severe calcification, and high thrombus load) is at the root of type Ia endoleak.…”
Section: ¤ ¤mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18] More recent studies carry lower rates of early conversion, likely due to improvement in endografts and endovascular skills, better patient selection, and the trend toward treating most complications by endovascular means. 24 Mortality rates of early conversion vary between 0% and 28.5% (Table 1).…”
Section: Early Conversionmentioning
confidence: 99%